1993
DOI: 10.1111/j.1464-410x.1993.tb00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs a Prostatectomy? Review of a Waiting List

Abstract: A total of 118 patients on a waiting list for a transurethral prostatectomy, who had been selected primarily on the basis of their symptoms and the finding of an enlarged prostate, were reassessed by objective tests. Of the 107 finally studied, 44% were retained on the waiting list and a further 8% kept under review; 48% were discharged from any further follow-up. The study reinforces the importance of objectively assessing patients presenting with urinary symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Urinary retention or recur rent urinary tract infection is an indication to treat, but not necessarily by surgery [10], It is interesting to note that 48% of the patients on a waiting list for a TURP could be discharged from any further follow-up, empha sizing the importance of a better objective assessment of patients presenting with lower urinary tract symptoms before deciding on any form of treatment [11], A pressure flow study undeniably will confirm the presence or absence of infravesical obstruction ( fig. 2).…”
Section: Indications For Treatmentmentioning
confidence: 99%
“…Urinary retention or recur rent urinary tract infection is an indication to treat, but not necessarily by surgery [10], It is interesting to note that 48% of the patients on a waiting list for a TURP could be discharged from any further follow-up, empha sizing the importance of a better objective assessment of patients presenting with lower urinary tract symptoms before deciding on any form of treatment [11], A pressure flow study undeniably will confirm the presence or absence of infravesical obstruction ( fig. 2).…”
Section: Indications For Treatmentmentioning
confidence: 99%
“…Symptoms and postvoiding residual volume (PVR) correlate poorly with BOO, 6,7 and despite its widespread use, 8 urine flow rate has unclear diagnostic accuracy and utility for BOO 9 . Investigators have found that flow rate does 7 and does not correlate 6,10–13 with urodynamically defined BOO; predicts 14–17 and fails to predict 18,19 outcome from transurethral prostatectomy; and should 8,16,20–22 and should not be used 12,23 as a screening test for BOO. Methodological differences between studies regarding subject selection, definitions for BOO, and correction of flow rate for voided volume compound the confusion further.…”
mentioning
confidence: 99%